1445. Impact of 10-Valent Pneumococcal Conjugate Vaccine Introduction on Pneumococcal Carriage and Antibiotic Susceptibility Patterns Among Children Aged <5 Years and Adults with HIV Infection, Kenya 2009–2013. (26th November 2018) - Kobayashi, Miwako; Kim, Lindsay; Bigogo, Godfrey; Ondari, Daniel; Conklin, Laura; Odoyo, Arthur; Odiembo, Herine; Pimenta, Fabiana; Ouma, Dominic; Harris, Aaron; Odero, Kennedy; Milucky, Jennifer; et al.
Abstract: Background: Kenya introduced 10-valent pneumococcal conjugate vaccine (PCV10) in 2011 (three doses at ages 6, 10, and 14 weeks). Impact of PCV10 on pneumococcal carriage was unknown in this setting. We assessed changes in pneumococcal carriage and antibiotic susceptibility in children aged < 5 years (U5) and HIV-infected adults (HIV+ adults) post-PCV10 introduction. Methods: During 2009–2013, we performed annual cross-sectional pneumococcal carriage surveys in two sites with ongoing population-based surveillance: Kibera (U5 only) and Lwak (U5 and HIV+ adults, catch-up vaccination for children 1–4 years offered in 2011). Nasopharyngeal swabs (and oropharyngeal swabs in adults) were obtained for culture. Pneumococcal isolates were serotyped by multiplex PCR and Quellung. Antibiotic susceptibility was determined (2009 and 2013). We calculated changes in penicillin nonsusceptible (intermediate or resistant) pneumococci (PNSP) carriage by chi-squared test. Changes in PCV10-type (VT) pneumococcal carriage in 2013 compared with baseline (U5: 2009–10, adults: 2009 only) were calculated by modified Poisson regression by age and site. Results: Overall, 2, 962 U5 (2, 073 in Kibera, 889 in Lwak) and 2, 028 HIV+ adults were enrolled. VT carriage declined by 52–60% in children 1–4 years, by 60% in children < 1 year in Kibera, and by 76% in HIV+ adults (table). PNSP carriage declined from 32.8% to 22.3% ( P < 0.01) in HIV+ adults but did not change in U5 (Kibera: 77.0% vs. 75.5%, P =0.10; Lwak: 74.3% vs. 74.6%, P = 0.94). Conclusion: The infant PCV10 program was associated with declines in VT carriage among U5 and HIV+ adults, and declines in PNSP carriage among HIV+ adults; however, VT carriage remained >10% among U5 2 years post-PCV10 introduction. Disclosures: All authors: No reported disclosures.